Case-control study of 24 hour ambulatory blood pressure in patients with obstructive sleep apnoea and normal matched control subjects. Issue 9 (1st September 2000) - Davies, Christopher W H; Crosby, Joy H; Mullins, Rebecca L; Barbour, Charles; Davies, Robert J O; Stradling, John R
Abstract : BACKGROUND: There is considerable debate regarding the relationship between obstructive sleep apnoea (OSA) and hypertension. It is unclear whether OSA is an independent vascular risk factor as studies attempting to assess this association have produced conflicting results because of confounding variables such as upper body obesity, alcohol, and smoking. A case-control study of 24 hour ambulatory blood pressure was undertaken in patients with OSA and matched controls to assess whether OSA is an independent correlate of diurnal hypertension. METHODS: Forty five patients with moderate to severe OSA and excessive daytime sleepiness were matched with 45 controls without OSA in a sleep study. Matched variables included age, body mass index (BMI), alcohol, cigarette usage, treated hypertension, and ischaemic heart disease. Upper body obesity was compared by waist:hip and waist:height ratios; 24 hour ambulatory blood pressure recordings were performed (before treatment for OSA) in all subjects. RESULTS: Patients with OSA had significantly increased mean (SD) diastolic blood pressure (mm Hg) during both daytime (87.4 (10.2) versus 82.8 (9.1); p=0.03, mean difference 4.6 (95% CI 0.7 to 8.6) and night time (78.6 (9.3) versus 71.4 (8.0); p<0.001, mean difference 7.2 (95% CI 3.7 to 10.6)), and higher systolic blood pressure at night (119.4 (20.7) versus 110.2 (13.9); p=0.01, mean difference 9.2 (95% CI 2.3 to 16.1)). The nocturnal reduction in blood pressure ("dipping") was smaller in patients with OSA than in control subjects. CONCLUSIONS: Compared with closely matched control subjects, patients with OSA have increased ambulatory diastolic blood pressure during both day and night, and increased systolic blood pressure at night. The magnitude of these differences is sufficient to carry an increased risk of cardiovascular morbidity. The slight excess of upper body fat deposition in the controls may make these results conservative.